2010
DOI: 10.4196/kjpp.2010.14.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stretch-Induced Protection against Myocardial Ischemia-Reperfusion Injury Involves AMP-Activated Protein Kinase

Abstract: AMP-activated protein kinase (AMPK) protects various tissues and cells from ischemic insults andis activated by many stimuli including mechanical stretch. Therefore, this study investigated if the activation of AMPK is involved in stretch-induced cardioprotection (SIC). Intraventricular balloon and aorto-caval shunt (ACS) were used to stretch rat hearts ex vivo and in vivo, respectively. Stretch preconditioning reduced myocardial infarct induced by ischemia-reperfusion (I/R) and improved post-ischemic function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
5
0
5
Order By: Relevance
“…We next sought to determine the mechanosensitive signaling pathway that couples dystrophin to stretchinduced activation of nNOS. AMP-activated protein kinase (AMPK) phosphorylates nNOS-serine 1412 in multiple cell types, including skeletal muscle (40)(41)(42)(43), and can be activated by mechanical stimulation of cardiac muscle (44,45). Therefore, we investigated the involvement of AMPK in dystrophin-dependent mechano-nNOS signaling in cardiomyocytes.…”
Section: Stretch-induced Nnos Phosphorylation Is Impaired In Dystrophin-mentioning
confidence: 99%
“…We next sought to determine the mechanosensitive signaling pathway that couples dystrophin to stretchinduced activation of nNOS. AMP-activated protein kinase (AMPK) phosphorylates nNOS-serine 1412 in multiple cell types, including skeletal muscle (40)(41)(42)(43), and can be activated by mechanical stimulation of cardiac muscle (44,45). Therefore, we investigated the involvement of AMPK in dystrophin-dependent mechano-nNOS signaling in cardiomyocytes.…”
Section: Stretch-induced Nnos Phosphorylation Is Impaired In Dystrophin-mentioning
confidence: 99%
“…In addition, a previous study has suggested that stretch-activated ion channels also play a key role in cardiac pathophysiology [42] , and GdCl 3 is the most widely used antagonist of this channel. Abnormal tissue stretch is a classical feature of myocardial I/R [21,43] . Therefore, the antagonism effect of GdCl 3 on stretchactivated ion channels may also reflect another advantage of GdCl 3 over other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that pharmacological preconditioning of the heart with the K ATP channel opener diazoxide is lost in Kir6.2 Ϫ/Ϫ hearts (52), suggesting that diazoxide is acting primarily through induction of cardioprotective mechanisms associated with plasma membrane K ATP channel activity. Interestingly, it has been shown that AMPK activation plays a key role in mediating the effects of classical ischemic preconditioning (32,47) and stretch-induced preconditioning (24). Therefore, we tested whether the observed diazoxideinduced activation of AMPK is lost in Kir6.2 Ϫ/Ϫ hearts.…”
Section: Pharmacological Activation Of Ampk Is Impaired In Kir62 ϫ/ϫmentioning
confidence: 96%